Merdeka Belajar Untuk Menumbuhkan Kearifan Lokal: Suatu Proses Pembelajaran Memperkuat Pilar Pendidikan - Kusnadi (Prosiding Temu Ilmiah Nasional Guru, 2022)
This article aims to discuss the Freedom to Learn Program to foster local wisdom, as an alternative learning to strengthen the pillars of education. Through this program, the Ministry of Education and Culture strengthens a number of aspects of education. By using the Merdeka Learning method, students can choose the subjects they are interested in. In particular, Indonesian education does not foster ineffective learning or unequal student participation. By not neglecting them and instead incorporating local expertise into the learning process, better educational infrastructure and technology can help achieve the three self-directed learning metrics. The infrastructure of the new class must be more advanced than the old one. The method used in analyzing this article is a literature study. To make it easier for students and teachers to develop their own potential, it is necessary to have the existence and involvement of local culture around their living environment, in this case how local wisdom becomes part of the learning process in the independent learning program. This article also discusses how independent learning as a model of educational development, local wisdom as an inspirational source for independent learning, and independent learning grows local wisdom to strengthen the pillars of education.